Analysis Teaching Vocabulary on Semantic Mapping for English Club in Vocational High School - Ahmad Darussalam (Borneo Educational Journal (Borju), 2022)
The aims of this study were to watch the phenomenon of semantic mapping to teach vocabulary applied by the teacher and the result of the semantic mapping used by teacher. The method of this research is case study. Case study was to learn as much as possible about an individual or group so that the information can be generalized to many others. For gathering the data, researcher used triangulation method. There were from observation, interviews and questionnaire. Interview and observation elaborated the information gathered from questionnaire. First, semantic mapping represent the ideas of views from the student in pairs easily. Second, the strategy helped the student to brainstorm and generate the idea or knowledge. Third, student motivated to increase the concepts and discover the proposition on related words. Fourth, the semantic map allowed the student to communicate actively in pairs and complete the information each other. Fifth, the student participated actively to present their comment. Sixth, the semantic map discover